2016
DOI: 10.1039/c6ra10856c
|View full text |Cite
|
Sign up to set email alerts
|

One-pot controllable synthesis of carboxylic group functionalized hollow mesoporous silica nanospheres for efficient cisplatin delivery

Abstract: A simple one-pot synthesis and functionalization of HMSNs with COOH as a sustained and controlled release drug delivery system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Farsangi et al prepared HMSNP-COOH carriers and loaded cisplatin in them via coordination bonds between carboxylic groups and Pt atoms in cisplatin molecules. 42 These nanomedicines had a pH-dependent release pattern with drug-loading content as high as 48 wt%.…”
Section: Mesoporous Silica-based Materials As Carriersmentioning
confidence: 99%
“…Farsangi et al prepared HMSNP-COOH carriers and loaded cisplatin in them via coordination bonds between carboxylic groups and Pt atoms in cisplatin molecules. 42 These nanomedicines had a pH-dependent release pattern with drug-loading content as high as 48 wt%.…”
Section: Mesoporous Silica-based Materials As Carriersmentioning
confidence: 99%
“…Comparing the spectrum of NH 2 -Pr-SBA-15 to that of E-NH 2 -Pr-SBA-15 nanobiocomposite, the increase in the intensities of the peaks around 2930 and 600 cm -1 might be attributed to the C-H and N-H stretching vibrations of the lipase enzyme [46]. Besides, the appearance of peaks within 1780 to 1860 cm -1 would be attributed to the C�O of peptide and carboxylic moieties in the lipase enzyme [50]. Te increase in intensities of peaks around 1440 and 1530 cm -1 besides the appearance of the peak around 1640 cm -1 indicates-CH and-NH 2 moieties of the lipase enzyme [21].…”
Section: Te Stability Of the Prepared E-nhmentioning
confidence: 91%
“…136 Cisplatin, a chemotherapeutic agent used for various types of cancer, has been employed on a variety of SiO 2 mesoporous supports. [45][46][47] Gu et al demonstrated that COOH-MCM-41 enhanced the adsorption of this drug which exhibited a higher antitumor activity and more accumulation in HeLa cells when compared to free cisplatin. 45 In particular, they followed the uptake of Pt in HeLa cells using ICP-AES as shown in Fig.…”
Section: Drug Deliverymentioning
confidence: 99%
“…46 Jomeh Farsangi et al used double templated mesoporous SiO 2 modified with CES observing slowrelease cisplatin profiles which can be accelerated when lowering the pH of the solution, an interesting feature as cancerous cells have a low pH environment. 47 Delivery is not restricted to medicinal components alone: herbicides such as 2,4-D and picloram have also been evaluated. 186 Given that surface charge of the oxide framework can be easily tuned with the solution pH, Saikia et al devised the selective adsorption of two proteins with different isoelectric points, papain (pI B 8.75) and hemoglobin (pI B 6.8).…”
Section: Drug Deliverymentioning
confidence: 99%